2017
DOI: 10.1186/s40795-017-0172-0
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of a randomized controlled trial of nutrition education to promote farmers’ market fruit and vegetable purchases and consumption among women enrolled in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC)

Abstract: Background: The Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) provides participants seasonal Farmers' Market Nutrition Program (FMNP) vouchers to purchase fruits and vegetables (FV) at farmers' markets and monthly cash value vouchers (CVV) redeemable at farmers' markets. Despite the promise of FMNP vouchers and CVV for improving FV access among WIC participants, voucher redemption rates are low. This study evaluated WIC Fresh Start (WFS), a theory-driven, web-based lesson to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(38 reference statements)
0
6
1
Order By: Relevance
“…Nevertheless, the observed difference is practically meaningful considering the modest scope of the project. The fifty CVV redeemed at the on-site market is noteworthy, exceeding the number redeemed in our earlier intervention research examining the effects of nutrition education on the redemption CVV at farmers' markets (32) . The higher number of CVV redeemed in the present study highlights the promise of combining nutrition education with improved access via the WIC-based market.…”
Section: Discussioncontrasting
confidence: 54%
See 2 more Smart Citations
“…Nevertheless, the observed difference is practically meaningful considering the modest scope of the project. The fifty CVV redeemed at the on-site market is noteworthy, exceeding the number redeemed in our earlier intervention research examining the effects of nutrition education on the redemption CVV at farmers' markets (32) . The higher number of CVV redeemed in the present study highlights the promise of combining nutrition education with improved access via the WIC-based market.…”
Section: Discussioncontrasting
confidence: 54%
“…1. Our earlier research with women served by the collaborating agency revealed that participants' vegetable (but not fruit) intake was below recommended levels (32,36,37) . Therefore, the focus of intervention was promoting vegetable intake.…”
Section: Guiding Theoretical Framework and Intervention Componentsmentioning
confidence: 92%
See 1 more Smart Citation
“…Differences in mean sales were reported for individual stands and the overall market, but no empirical tests were conducted to verify the statistical significance of study findings. A few additional studies tested the effectiveness of coupons, but only on SNAP participants (Di Noia et al, 2017; Payne et al, 2013; Racine et al, 2010), and not on coupons' ability to increase overall market participation.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, WIC provides participants seasonal Farmers' Market Nutrition Program (FMNP) vouchers to purchase fruits and vegetables (FV) at farmers' markets and monthly cash value vouchers (CVV) redeemable at farmers' markets. Despite the promise of FMNP vouchers and CVV for improving FV access among WIC participants, voucher redemption rates are low [11].…”
Section: Introductionmentioning
confidence: 99%